How Aware is Generation Z of Waqf? A Quantitative Study on Maqashid among Indonesian Muslim Students - Rachmawati, Andini; Rofiqo, Azidni; Mudi Awalia, Fadhila Tianti; Aqidah, Nurul (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
This study aims to measure the influence of waqf literacy, relative advantage, religiosity, and attitude on waqf intention among Generation Z, specifically Muslim university students in Indonesia. The respondents were 505 Gen-Z students, specifically Muslim students born between 1996 and 2012 in Indonesia who have ever donated to waqf, with primary data collected through questionnaires and analyzed using the Structural Equation Modelling-Partial Least Squares (SEM-PLS) technique. In addition, the data were also analyzed using maqashid sharia theory to see the impact of waqf benefits on individuals and society in general. The results show that waqf literacy, perceived benefits of waqf activities, and religiosity level positively contribute to individuals' attitudes towards waqf, influencing Generation Z's intention to participate in waqf activities. As a form of charity derived from the Prophet Muhammad's sunnah, waqf is essential in achieving the maqashid, particularly in protecting wealth (hifz al-mal) and improving social welfare. Therefore, increasing waqf literacy through programs such as the Indonesian Waqf Awareness Movement (GISWAF), as well as improving convenience, accessibility, and regulatory clarity in waqf practices, are proposed to strengthen positive attitudes towards waqf and encourage greater participation of Generation Z in waqf activities.